Influence of Capital Structure Choice on Firm Performance: A Case of Listed Non-Financial Firms of Pakistan - ur Rehman, Zia; Ayub Siddiqui, Muhammad; Khan, Asad (The Journal of Humanities & Social Sciences, 2022)
Capital structure and its relation with firm value continue to attract researcher’s interest around the world to get deeper understanding on the matter concerned. The aim of this paper is to empirically investigate whether capital structure choice influences firm profitability or not in listed non-financial firms of Pakistan. Panel data regression (fixed effects model) was used to examine the relationship and effect of capital structure choice and firm performance. Secondary data from 2008-2013 was used for this study. The findings of the study revealed that capital structure choice measured through short-term debt (STD), long-term debt (LTD) and total debt (TD) has a negative but statistically weak relationship with firm performance measured through ROA and ROE. In case of firm performance measured through GPR, capital structure choice measured through LTD and TD shows positive and statistically significant relationship with firm performance whereas in case of STD it is negative but statistically significant.